Determining Employee Job Satisfaction and Work Productivity: An Analysis of HR Competency and Organizational Culture at PT. XYZ - Wisnu, R Wisnu Prio Pamungkas (Dinasti International Journal of Management Science, 2024)
This study examines the impact of human resource competencies and organizational culture on employee job satisfaction and employee work productivity at PT. XYZ, an entity in the public service sector. Utilizing a literature review approach, this research evaluates how HR competencies and organizational culture directly affect employee job satisfaction and employee work productivity as intervening and dependent variables. The method applied involves an in-depth analysis of existing theories and previous empirical research, enabling the identification of key indicators that influence both outcomes. The findings of this study reveal a positive and significant correlation between HR competencies, including information technology competencies, and organizational culture on employee job satisfaction, which in turn enhances employee work productivity. These results provide crucial insights for strategic decision-making at PT. XYZ and contribute to the academic literature in human resource management and organization